Metal coordination carbon sphere material with molecular imprinting for removing boric acid in water body and preparation method thereof

CN120054435BActive Publication Date: 2026-10-16QINGDAO UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510328669.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2026-10-16
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

然而,传统的分子印迹材料通常依赖于有机聚合物作为基质,其机械强度和热稳定性较差,限制了其在高温或苛刻环境下的应用

Benefits of technology

[0022] (1) This invention provides a method for preparing molecularly imprinted metal-coordinated carbon spheres for removing boric acid from water. First, phenolic resin spheres are prepared using formaldehyde and phenol as raw materials. Then, the phenolic resin spheres are carbonized to obtain phenolic resin carbon spheres. The purpose is to first carbonize and then functionalize them so that the active sites of tannic acid on the carbon spheres can interact with Zr. 4+Metal coordination occurs, and the remaining uncoordinated sites can chelate with boric acid. Phenolic resin carbon spheres are then dispersed in a tannic acid-ethanol solution. The phenolic resin carbon spheres exhibit excellent sphericity and thermal stability, while the tannic acid-ethanol solution is rich in polyphenolic hydroxyl structures, which can form stable coordination bonds with the subsequent metal ion solution, thereby constructing a metal-organic framework structure. Furthermore, it can adsorb boric acid to form chelate bonds. Using phenolic resin and tannic acid as the main raw materials, this method further realizes the high-value utilization of natural polyphenols, providing a new approach for the preparation of molecularly imprinted materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120054435B_ABST
    Figure CN120054435B_ABST
Patent Text Reader

Abstract

The application discloses a metal coordination carbon sphere material with molecular imprinting for removing boric acid in a water body and a preparation method, and relates to the technical field of preparation of adsorbing materials. The method comprises the following steps: preparing a phenolic resin sphere by taking formaldehyde and phenol as raw materials, and carbonizing the phenolic resin sphere to obtain a phenolic resin carbon sphere; then introducing tannic acid to obtain a tannic acid modified phenolic resin carbon sphere; dispersing the tannic acid modified phenolic resin carbon sphere in a metal salt solution, so that the metal ions in the metal salt solution and the oxygen atoms in the tannic acid undergo a coordination reaction to form a metal-organic framework structure; and finally performing molecular imprinting treatment on the formed metal coordination phenolic resin carbon sphere by taking boric acid as a template molecule. The metal coordination carbon sphere material with molecular imprinting prepared by the application has high adsorbing performance and selectivity for boric acid, and is suitable for treatment of natural water samples and industrial wastewater containing boric acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of adsorption material preparation technology, specifically to a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water and its preparation method. Background Technology

[0002] With rapid industrial development, the pollution problem of boric acid in water bodies has become increasingly serious. Boric acid is a toxic and harmful substance that poses a potential threat to the ecological environment and human health. Among many materials, carbon materials, due to their unique physicochemical properties such as high specific surface area, good chemical stability, and conductivity, have broad application prospects in adsorption, separation, catalysis, and other fields. However, traditional carbon materials often lack the selective adsorption capacity for specific target molecules, which limits their application in some scenarios where high selectivity is required.

[0003] To improve the selectivity of carbon sphere materials, molecular imprinting technology (MIT) has been introduced into materials design. Molecular imprinting technology enables efficient recognition and adsorption of specific molecules by constructing recognition sites on the material surface that match the shape, size, and functional groups of the target molecule. However, traditional molecularly imprinted materials typically rely on organic polymers as a matrix, which have poor mechanical strength and thermal stability, limiting their application in high-temperature or harsh environments. Summary of the Invention

[0004] One of the objectives of this invention is to provide a method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water. The metal-organic coordination structure formed not only enhances the stability of the carbon sphere material, but also provides abundant active sites for subsequent molecular imprinting, thereby improving the removal rate of boric acid from water.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] A method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water comprises the following steps:

[0007] a. Preparation of phenolic resin balls using formaldehyde and phenol as raw materials;

[0008] b. The phenolic resin balls are carbonized at a carbonization temperature of 700-900℃ under argon protection to obtain phenolic resin carbon balls.

[0009] c. Disperse phenolic resin carbon balls in tannic acid ethanol solution and react for a period of time to allow tannic acid to be fully adsorbed on the surface of phenolic resin carbon balls, thereby obtaining tannic acid modified phenolic resin carbon balls.

[0010] d. Disperse tannic acid-modified phenolic resin carbon spheres in a metal salt solution, adjust the pH of the solution to 5-6, and stir the reaction at room temperature for 20-25 hours to allow the metal ions in the metal salt solution to coordinate with the oxygen atoms in the tannic acid to form a metal-organic framework structure. After the reaction is complete, metal-coordinated phenolic resin carbon spheres are obtained.

[0011] e. Disperse metal-coordinated phenolic resin carbon spheres in a boric acid solution, so that the boric acid is in the form of B(OH)4 - The boric acid template molecules exist in the form of tannic acid and are adsorbed onto the tannic acid and metal coordination sites of the metal-coordinated phenolic resin carbon spheres to obtain carbon spheres adsorbed with boric acid template molecules; the carbon spheres adsorbed with boric acid template molecules are dispersed in an ethanol solution containing a crosslinking agent and an initiator, and a polymerization reaction is carried out at a certain temperature to further fix the boric acid template molecules to obtain crosslinked polymerized carbon spheres.

[0012] f. Disperse the cross-linked polymerized carbon spheres in an acidic solution, elute the boric acid template molecules, and dry to obtain a metal-coordinated carbon sphere material with molecular imprinting.

[0013] The preparation method of the above-mentioned molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water includes the following steps in step a: formaldehyde and phenol are mixed and stirred at a molar ratio of 1.2:1, heated to 90-110℃, a dispersant is added and stirred for 20-40 min, a crosslinking agent is added and stirred for 3-5 h; after the reaction is completed, the crosslinked product is transferred to a centrifuge tube, the supernatant is discarded by centrifugation, and the collected prepolymer solution is washed and dried to obtain phenolic resin spheres.

[0014] The above-mentioned method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water, wherein the dispersant is polyvinyl alcohol and the crosslinking agent is hexamethylenetetramine.

[0015] In the preparation method of the molecularly imprinted metal coordination carbon sphere material for removing boric acid from water, step b involves a carbonization heating rate of 4–6 °C / min and a carbonization time of 1–3 h. After carbonization, the material is naturally cooled to room temperature, and the resulting carbon spheres are washed and dried with deionized water and ethanol to obtain phenolic resin carbon spheres.

[0016] In the preparation method of the above-mentioned molecularly imprinted metal coordination carbon sphere material for removing boric acid from water, in step c, the solid-liquid ratio of phenolic resin carbon spheres to tannic acid ethanol solution is 1:10 g / mL, that is, 1 g of phenolic resin carbon spheres are dispersed in 10 mL of tannic acid ethanol solution; the concentration of tannic acid ethanol solution is 4-6 g / L; the two are stirred and reacted at 200-400 rpm for 10-15 h.

[0017] In the above-mentioned method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water, in step d, the metal salt solution is a ZrCl4 solution or a FeCl3 solution.

[0018] The above-mentioned method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water involves a solid-liquid ratio of tannic acid-modified phenolic resin carbon spheres to a metal salt solution of 1:100 g / mL, i.e., 1 g of tannic acid-modified phenolic resin carbon spheres are dispersed in 100 mL of a metal salt solution; the metal salt solution is a ZrCl4 solution with a concentration of 0.05 mol / L.

[0019] In the above-mentioned method for preparing molecularly imprinted metal-coordinated carbon spheres for removing boric acid from water, in step e, the solid-liquid ratio of the metal-coordinated phenolic resin carbon spheres to the boric acid solution is 1:30 g / mL, that is, 1 g of metal-coordinated phenolic resin carbon spheres are dispersed in 30 mL of boric acid solution; the concentration of the boric acid solution is 0.1 mol / L; the crosslinking agent is 0.1 mol / L ethylene glycol dimethacrylate; and the initiator is 0.02 mol / L potassium persulfate. In step f, the acidic solution is a 0.1 mol / L hydrochloric acid solution, and the pH is adjusted to 2-3 using the hydrochloric acid solution.

[0020] Another object of the present invention is to provide a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water, which is prepared by the above-described method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water.

[0021] Compared with the prior art, the present invention brings the following beneficial technical effects:

[0022] (1) This invention provides a method for preparing molecularly imprinted metal-coordinated carbon spheres for removing boric acid from water. First, phenolic resin spheres are prepared using formaldehyde and phenol as raw materials. Then, the phenolic resin spheres are carbonized to obtain phenolic resin carbon spheres. The purpose is to first carbonize and then functionalize them so that the active sites of tannic acid on the carbon spheres can interact with Zr. 4+Metal coordination occurs, and the remaining uncoordinated sites can chelate with boric acid. Phenolic resin carbon spheres are then dispersed in a tannic acid-ethanol solution. The phenolic resin carbon spheres exhibit excellent sphericity and thermal stability, while the tannic acid-ethanol solution is rich in polyphenolic hydroxyl structures, which can form stable coordination bonds with the subsequent metal ion solution, thereby constructing a metal-organic framework structure. Furthermore, it can adsorb boric acid to form chelate bonds. Using phenolic resin and tannic acid as the main raw materials, this method further realizes the high-value utilization of natural polyphenols, providing a new approach for the preparation of molecularly imprinted materials.

[0023] (2) In this invention, metal ions in metal salt solution coordinate with oxygen atoms in tannic acid to form a metal-organic coordination structure. This structure not only enhances the stability of the material, but also provides abundant active sites for subsequent molecular imprinting. In addition, by eluting boric acid template molecules, this invention forms a porous structure, which improves the pore distribution and specific surface area of ​​the carbon ball material, and significantly enhances the adsorption performance and molecular recognition ability of the material.

[0024] (3) The molecularly imprinted metal-coordinated carbon sphere material prepared in this invention exhibits excellent selective adsorption performance in boron removal applications. The molecularly imprinted cavities on the material surface can accurately identify and adsorb boron molecules, while Zr 4+ The coordination effect further enhances the adsorption capacity of the material. Compared with traditional adsorption materials, the material of this invention not only has higher adsorption capacity and selectivity, but also good stability and regeneration performance, and can be widely used in water treatment, environmental remediation and other fields, providing a new solution for the efficient treatment of boron pollution. Attached Figure Description

[0025] The present invention will be further described below with reference to the accompanying drawings:

[0026] Figure 1 This is a scanning electron microscope image of the material from Example 1.

[0027] Figure 2 The chart shows a comparison of the adsorption selectivity of the materials prepared in Examples 1-3 and Comparative Examples 1-4 for boric acid, oxalic acid, and citric acid.

[0028] Figure 3 The graphs show the stability of the materials prepared in Examples 1-3 and Comparative Examples 1-4 after multiple adsorption-desorption cycles. Detailed Implementation

[0029] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings.

[0030] All the raw materials required for this invention can be purchased through commercial channels.

[0031] The main technical concept of this invention is that by introducing metal coordination into phenolic resin carbon spheres, a metal-organic coordination structure is formed. This structure can not only enhance the mechanical properties and thermal stability of the material, but also further improve the selective recognition ability of the material through the synergistic effect of metal and organic ligands.

[0032] Example 1:

[0033] A method for preparing molecularly imprinted metal-coordinated carbon spheres for removing boric acid from water includes the following steps:

[0034] Step 1: Weigh formaldehyde and phenol at a molar ratio of 1.2:1 and add them to a 500mL three-necked flask. Attach the stirrer, thermometer, and reflux condenser. Turn on the magnetic stirrer and stir at 550rpm while simultaneously heating to 100℃. Add 0.5g of polyvinyl alcohol (PVA) as a dispersant and continue stirring for 30 minutes. Then add 1.0g of hexamethylenetetramine (HMTA) as a crosslinking agent and continue stirring for 4 hours to obtain a prepolymer solution. After the reaction is complete, transfer the product from the three-necked flask to a centrifuge tube and centrifuge at 4000rpm for 10 minutes, discarding the supernatant. Wash the precipitate three times with deionized water, adding 50mL of deionized water each time, shaking well, and then centrifuging. Then wash three times with anhydrous ethanol, adding 50mL of anhydrous ethanol each time, shaking well, and then centrifuging. Transfer the washed precipitate to a petri dish and dry it in a vacuum drying oven at 105℃ for 24 hours to obtain dried phenolic resin balls.

[0035] Step 2: Place the phenolic resin balls obtained in Step 1 into a high-temperature carbonization furnace and heat them to 800°C at a heating rate of 5°C / min. Carbonize them for 2 hours under argon protection (argon flow rate of 50 mL / min) to obtain phenolic resin carbon balls. Allow them to cool naturally to room temperature, remove the phenolic resin carbon balls, wash them three times with deionized water and ethanol respectively, and dry them for later use.

[0036] Step 3: Disperse the phenolic resin carbon balls obtained in Step 2 in a 4-6 g / L tannic acid ethanol solution; stir the mixture at 300 rpm for 12 hours at room temperature using a magnetic stirrer to allow the tannic acid to be fully adsorbed onto the surface of the phenolic resin carbon balls; after the reaction is complete, wash the mixture three times with deionized water and ethanol respectively to remove unreacted tannic acid, and obtain tannic acid modified phenolic resin carbon balls.

[0037] Step 4: Disperse the tannic acid-modified phenolic resin carbon spheres obtained in Step 3 in 100 mL of 0.05 mol / L ZrCl4 solution; adjust the pH of the solution to 5-6 with dilute hydrochloric acid, and stir the mixture at 300 rpm with a magnetic stirrer for 24 hours at room temperature to allow the Zr... 4+It undergoes a coordination reaction with oxygen atoms in tannic acid to form a metal-organic framework (MOF) structure. After the reaction is complete, it is washed three times with deionized water and ethanol respectively to remove uncoordinated metal ions, and metal-coordinated phenolic resin carbon spheres are obtained.

[0038] Step 5: Disperse the metal-coordinated phenolic resin carbon spheres obtained in Step 4 in 100 mL of 0.1 mol / L boric acid aqueous solution; adjust the pH to 9-10 with sodium hydroxide solution, and stir the reaction at room temperature for 24 hours to allow the boric acid to react as B(OH)4. - The boric acid exists in the form of tannic acid template molecules and adsorbs onto the tannic acid and metal coordination sites on the surface of the carbon spheres. After the reaction, the spheres are washed three times with deionized water to remove unadsorbed boric acid. The carbon spheres with adsorbed boric acid template molecules are dispersed in an ethanol solution containing 0.1 mol / L ethylene glycol dimethacrylate and 0.02 mol / L potassium persulfate. The mixture is stirred at 60°C for 6 hours to allow the crosslinking agent to polymerize under the action of the initiator, thus fixing the boric acid template molecules onto the surface of the carbon spheres. After the reaction, the spheres are washed three times each with ethanol and deionized water to remove unreacted crosslinking agent and initiator.

[0039] Step 6: Disperse the cross-linked polymerized carbon spheres obtained in Step 5 in 100 mL of 0.1 mol / L hydrochloric acid solution; adjust the pH of the solution to 2-3, stir the reaction at room temperature for 2 hours to elute the boric acid template molecules from the surface of the carbon spheres; wash three times with deionized water and ethanol respectively to remove residual acid, and dry to obtain a metal-coordinated carbon sphere material with molecular imprints.

[0040] The scanning electron microscope image of the carbon sphere material prepared in this embodiment is shown below. Figure 1 As shown.

[0041] Example 2:

[0042] A method for preparing molecularly imprinted metal-coordinated carbon spheres for removing boric acid from water includes the following steps:

[0043] Step 1: Weigh formaldehyde and phenol at a molar ratio of 1.2:1 and add them to a 500mL three-necked flask. Attach the stirrer, thermometer, and reflux condenser. Turn on the magnetic stirrer and stir at 550rpm while simultaneously heating to 100℃. Add 0.5g of polyvinyl alcohol (PVA) as a dispersant and continue stirring for 30 minutes. Then add 1.0g of hexamethylenetetramine (HMTA) as a crosslinking agent and continue stirring for 4 hours to obtain a prepolymer solution. After the reaction is complete, transfer the product from the three-necked flask to a centrifuge tube and centrifuge at 4000rpm for 10 minutes, discarding the supernatant. Wash the precipitate three times with deionized water, adding 50mL of deionized water each time, shaking well, and then centrifuging. Then wash three times with anhydrous ethanol, adding 50mL of anhydrous ethanol each time, shaking well, and then centrifuging. Transfer the washed precipitate to a petri dish and dry it in a vacuum drying oven at 105℃ for 24 hours to obtain dried phenolic resin balls.

[0044] Step 2: Place the phenolic resin balls obtained in Step 1 into a high-temperature carbonization furnace and heat them to 700°C at a heating rate of 5°C / min. Carbonize them for 2 hours under argon protection (argon flow rate of 50 mL / min) to obtain phenolic resin carbon balls. Allow them to cool naturally to room temperature, remove the phenolic resin carbon balls, wash them three times with deionized water and ethanol respectively, and dry them for later use.

[0045] Step 3: Disperse the phenolic resin carbon balls obtained in Step 2 in a 4-6 g / L tannic acid ethanol solution; stir the mixture at 300 rpm for 12 hours at room temperature using a magnetic stirrer to allow the tannic acid to be fully adsorbed onto the surface of the phenolic resin carbon balls; after the reaction is complete, wash the mixture three times with deionized water and ethanol respectively to remove unreacted tannic acid, and obtain tannic acid modified phenolic resin carbon balls.

[0046] Step 4: Disperse the tannic acid-modified phenolic resin carbon spheres obtained in Step 3 in 100 mL of 0.05 mol / L ZrCl4 solution; adjust the pH of the solution to 5-6 with dilute hydrochloric acid, and stir the mixture at 300 rpm with a magnetic stirrer for 24 hours at room temperature to allow the Zr... 4+ It undergoes a coordination reaction with oxygen atoms in tannic acid to form a metal-organic framework (MOF) structure. After the reaction is complete, it is washed three times with deionized water and ethanol respectively to remove uncoordinated metal ions, and metal-coordinated phenolic resin carbon spheres are obtained.

[0047] Step 5: Disperse the metal-coordinated phenolic resin carbon spheres obtained in Step 4 in 100 mL of 0.1 mol / L boric acid aqueous solution; adjust the pH to 9-10 with sodium hydroxide solution, and stir the reaction at room temperature for 24 hours to allow the boric acid to react as B(OH)4. -The boric acid exists in the form of tannic acid template molecules and adsorbs onto the tannic acid and metal coordination sites on the surface of the carbon spheres. After the reaction, the spheres are washed three times with deionized water to remove unadsorbed boric acid. The carbon spheres with adsorbed boric acid template molecules are dispersed in an ethanol solution containing 0.1 mol / L ethylene glycol dimethacrylate and 0.02 mol / L potassium persulfate. The mixture is stirred at 60°C for 6 hours to allow the crosslinking agent to polymerize under the action of the initiator, thus fixing the boric acid template molecules onto the surface of the carbon spheres. After the reaction, the spheres are washed three times each with ethanol and deionized water to remove unreacted crosslinking agent and initiator.

[0048] Step 6: Disperse the cross-linked polymerized carbon spheres obtained in Step 5 in 100 mL of 0.1 mol / L hydrochloric acid solution; adjust the pH of the solution to 2-3, stir the reaction at room temperature for 2 hours to elute the boric acid template molecules from the surface of the carbon spheres; wash three times with deionized water and ethanol respectively to remove residual acid, and dry to obtain a metal-coordinated carbon sphere material with molecular imprints.

[0049] Example 3:

[0050] The difference from Example 1 is that:

[0051] In step four, the tannic acid-modified phenolic resin carbon spheres obtained in step three are dispersed in 100 mL of 0.05 mol / L FeCl3 solution; the pH of the solution is adjusted to 5-6 with dilute hydrochloric acid or sodium hydroxide solution, and the mixture is stirred at 300 rpm for 24 h at room temperature to allow the Fe... 3+ It undergoes a coordination reaction with the oxygen atom in tannic acid. After the reaction is complete, it is washed three times with deionized water and anhydrous ethanol, respectively, to remove uncoordinated metal ions.

[0052] Comparative Example 1:

[0053] A method for preparing carbon sphere material for removing boric acid from water specifically includes the following steps:

[0054] Step 1: Weigh formaldehyde and phenol at a molar ratio of 1.2:1 and add them to a 500mL three-necked flask. Attach the stirrer, thermometer, and reflux condenser. Turn on the magnetic stirrer and stir at 550rpm while simultaneously heating to 100℃. Add 0.5g of polyvinyl alcohol (PVA) as a dispersant and continue stirring for 30 minutes. Then add 1.0g of hexamethylenetetramine (HMTA) as a crosslinking agent and continue stirring for 4 hours to obtain a prepolymer solution. After the reaction is complete, transfer the product from the three-necked flask to a centrifuge tube and centrifuge at 4000rpm for 10 minutes, discarding the supernatant. Wash the precipitate three times with deionized water, adding 50mL of deionized water each time, shaking well, and then centrifuging. Then wash three times with anhydrous ethanol, adding 50mL of anhydrous ethanol each time, shaking well, and then centrifuging. Transfer the washed precipitate to a petri dish and dry it in a vacuum drying oven at 105℃ for 24 hours to obtain dried phenolic resin balls.

[0055] Step 2: Place the phenolic resin balls obtained in Step 1 into a high-temperature carbonization furnace and heat them to 800°C at a heating rate of 5°C / min. Carbonize them for 2 hours under argon protection (argon flow rate of 50 mL / min) to obtain phenolic resin carbon balls. Allow them to cool naturally to room temperature, remove the phenolic resin carbon balls, wash them three times with deionized water and ethanol respectively, and dry them for later use.

[0056] Step 3: Disperse the phenolic resin carbon balls obtained in Step 2 in a 4-6 g / L tannic acid ethanol solution; stir the mixture at 300 rpm for 12 hours at room temperature using a magnetic stirrer to allow the tannic acid to be fully adsorbed onto the surface of the phenolic resin carbon balls; after the reaction is complete, wash the mixture three times with deionized water and ethanol respectively to remove unreacted tannic acid, and obtain tannic acid modified phenolic resin carbon balls.

[0057] Step 4: Disperse the tannic acid-modified phenolic resin carbon spheres obtained in Step 3 in 100 mL of 0.05 mol / L ZrCl4 solution; adjust the pH of the solution to 5-6 with dilute hydrochloric acid, and stir the mixture at 300 rpm with a magnetic stirrer for 24 hours at room temperature to allow the Zr... 4+ It undergoes a coordination reaction with oxygen atoms in tannic acid to form a metal-organic framework (MOF) structure. After the reaction is complete, it is washed three times with deionized water and ethanol respectively to remove uncoordinated metal ions, and metal-coordinated phenolic resin carbon spheres are obtained.

[0058] Step 5: Disperse the metal-coordinated phenolic resin carbon spheres obtained in Step 4 in 100 mL of 0.1 mol / L boric acid aqueous solution; adjust the pH to 9-10 with sodium hydroxide solution, and stir the reaction at room temperature for 24 hours to allow the boric acid to react as B(OH)4. -The boric acid exists in the form of tannic acid and is adsorbed onto the tannic acid and metal coordination sites on the surface of the carbon spheres. After the reaction is complete, the spheres are washed three times with deionized water to remove the unadsorbed boric acid.

[0059] Step 6: Disperse the carbon spheres obtained in Step 5 in 100 mL of 0.1 mol / L hydrochloric acid solution; adjust the pH of the solution to 2-3, stir the reaction at room temperature for 2 hours to elute the boric acid template molecules from the surface of the carbon spheres; wash three times with deionized water and ethanol respectively to remove residual acid, and dry to obtain the metal-coordinated carbon sphere material with molecular imprints.

[0060] In this comparative example, the carbon spheres adsorbed with boric acid molecules did not undergo a cross-linking polymerization step. Instead, the template molecules were directly eluted, resulting in a molecularly imprinted metal-coordinated carbon sphere material. The boric acid template molecules were only physically adsorbed onto the carbon sphere surface and were not firmly fixed. During subsequent use, such as when eluting the template molecules or re-adsorbing, the boric acid molecules easily detached from the carbon sphere surface, failing to form stable molecularly imprinted vacancies. This led to a significant decrease in the material's selective adsorption performance for boric acid.

[0061] Comparative Example 2:

[0062] A method for preparing carbon sphere material for removing boric acid from water specifically includes the following steps:

[0063] Step 1: Weigh formaldehyde and phenol at a molar ratio of 1.2:1 and add them to a 500mL three-necked flask. Attach the stirrer, thermometer, and reflux condenser. Turn on the magnetic stirrer and stir at 550rpm while simultaneously heating to 100℃. Add 0.5g of polyvinyl alcohol (PVA) as a dispersant and continue stirring for 30 minutes. Then add 1.0g of hexamethylenetetramine (HMTA) as a crosslinking agent and continue stirring for 4 hours to obtain a prepolymer solution. After the reaction is complete, transfer the product from the three-necked flask to a centrifuge tube and centrifuge at 4000rpm for 10 minutes, discarding the supernatant. Wash the precipitate three times with deionized water, adding 50mL of deionized water each time, shaking well, and then centrifuging. Then wash three times with anhydrous ethanol, adding 50mL of anhydrous ethanol each time, shaking well, and then centrifuging. Transfer the washed precipitate to a petri dish and dry it in a vacuum drying oven at 105℃ for 24 hours to obtain dried phenolic resin balls.

[0064] Step 2: Place the phenolic resin balls obtained in Step 1 into a high-temperature carbonization furnace and heat them to 800°C at a heating rate of 5°C / min. Carbonize them for 2 hours under argon protection (argon flow rate of 50 mL / min) to obtain phenolic resin carbon balls. Allow them to cool naturally to room temperature, remove the phenolic resin carbon balls, wash them three times with deionized water and ethanol respectively, and dry them for later use.

[0065] Step 3: Disperse the phenolic resin carbon balls obtained in Step 2 in a 4-6 g / L tannic acid ethanol solution; stir the mixture at 300 rpm for 12 hours at room temperature using a magnetic stirrer to allow the tannic acid to be fully adsorbed onto the surface of the phenolic resin carbon balls; after the reaction is complete, wash the mixture three times with deionized water and ethanol respectively to remove unreacted tannic acid, and obtain tannic acid modified phenolic resin carbon balls.

[0066] Step 4: Disperse the tannic acid-modified phenolic resin carbon spheres obtained in Step 3 in 100 mL of 0.1 mol / L boric acid aqueous solution; adjust the pH value to 9-10 with sodium hydroxide solution, and stir the reaction at room temperature for 24 hours to allow the boric acid to react as B(OH)4. - The boric acid exists in the form of tannic acid template molecules and adsorbs onto the tannic acid and metal coordination sites on the surface of the carbon spheres. After the reaction, the spheres are washed three times with deionized water to remove unadsorbed boric acid. The carbon spheres with adsorbed boric acid template molecules are dispersed in an ethanol solution containing 0.1 mol / L ethylene glycol dimethacrylate and 0.02 mol / L potassium persulfate. The mixture is stirred at 60°C for 6 hours to allow the crosslinking agent to polymerize under the action of the initiator, thus fixing the boric acid template molecules onto the surface of the carbon spheres. After the reaction, the spheres are washed three times each with ethanol and deionized water to remove unreacted crosslinking agent and initiator.

[0067] Step 5: Disperse the cross-linked polymerized carbon spheres obtained in Step 4 in 100 mL of 0.1 mol / L hydrochloric acid solution; adjust the pH of the solution to 2-3, stir the reaction at room temperature for 2 hours to elute the boric acid template molecules from the surface of the carbon spheres; wash three times with deionized water and ethanol respectively to remove residual acid, and dry to obtain a metal-coordinated carbon sphere material with molecular imprints.

[0068] In this comparative example, no ZrCl4 solution was added to the tannic acid-modified phenolic resin carbon spheres, meaning no metal coordination reaction occurred. Experiments revealed that during high-temperature carbonization, the carbon spheres exhibited poor structural stability due to the lack of MOF structure support. During the adsorption of boric acid template molecules, the specific binding sites provided by the MOF structure could not be utilized, leading to a decrease in the adsorption capacity and selectivity of boric acid. Furthermore, the material was more prone to structural damage during repeated adsorption-desorption cycles.

[0069] Comparative Example 3:

[0070] A method for preparing carbon sphere material for removing boric acid from water specifically includes the following steps:

[0071] Step 1: Weigh formaldehyde and phenol at a molar ratio of 1.2:1 and add them to a 500mL three-necked flask. Attach the stirrer, thermometer, and reflux condenser. Turn on the magnetic stirrer and stir at 550rpm while simultaneously heating to 100℃. Add 0.5g of polyvinyl alcohol (PVA) as a dispersant and continue stirring for 30 minutes. Then add 1.0g of hexamethylenetetramine (HMTA) as a crosslinking agent and continue stirring for 4 hours to obtain a prepolymer solution. After the reaction is complete, transfer the product from the three-necked flask to a centrifuge tube and centrifuge at 4000rpm for 10 minutes, discarding the supernatant. Wash the precipitate three times with deionized water, adding 50mL of deionized water each time, shaking well, and then centrifuging. Then wash three times with anhydrous ethanol, adding 50mL of anhydrous ethanol each time, shaking well, and then centrifuging. Transfer the washed precipitate to a petri dish and dry it in a vacuum drying oven at 105℃ for 24 hours to obtain dried phenolic resin balls.

[0072] Step 2: Place the phenolic resin balls obtained in Step 1 into a high-temperature carbonization furnace and heat them to 800°C at a heating rate of 5°C / min. Carbonize them for 2 hours under argon protection (argon flow rate of 50 mL / min) to obtain phenolic resin carbon balls. Allow them to cool naturally to room temperature, remove the phenolic resin carbon balls, wash them three times with deionized water and ethanol respectively, and dry them for later use.

[0073] Step 3: Disperse the phenolic resin carbon balls obtained in Step 2 in a 4-6 g / L tannic acid ethanol solution; stir the mixture at 300 rpm for 12 hours at room temperature using a magnetic stirrer to allow the tannic acid to be fully adsorbed onto the surface of the phenolic resin carbon balls; after the reaction is complete, wash the mixture three times with deionized water and ethanol respectively to remove unreacted tannic acid, and obtain tannic acid modified phenolic resin carbon balls.

[0074] Step 4: Disperse the tannic acid-modified phenolic resin carbon spheres obtained in Step 3 in 100 mL of 0.05 mol / L ZrCl4 solution; adjust the pH of the solution to 5-6 with dilute hydrochloric acid, and stir the mixture at 300 rpm with a magnetic stirrer for 24 hours at room temperature to allow the Zr... 4+ It undergoes a coordination reaction with oxygen atoms in tannic acid to form a metal-organic framework (MOF) structure. After the reaction is complete, it is washed three times with deionized water and ethanol respectively to remove uncoordinated metal ions, thus obtaining metal-coordinated phenolic resin carbon spheres.

[0075] In this comparative example, the prepared metal-coordinated phenolic resin carbon spheres directly adsorbed boric acid without subsequent molecular imprinting or other operational steps. Due to the lack of molecular imprinted holes, the material lacked specific recognition ability for boric acid adsorption. It only relied on some physical and chemical adsorption effects on the surface of the carbon spheres, and the adsorption of boric acid and other interfering substances (such as oxalic acid and citric acid) was not very distinguishable, resulting in a significantly lower adsorption amount and selectivity coefficient of boric acid than in Example 1.

[0076] Comparative Example 4:

[0077] A method for preparing molecularly imprinted metal-coordinated carbon spheres for removing boric acid from water includes the following steps:

[0078] Step 1: Weigh formaldehyde and phenol at a molar ratio of 1.2:1 and add them to a 500mL three-necked flask. Attach the stirrer, thermometer, and reflux condenser. Turn on the magnetic stirrer and stir at 550rpm while simultaneously heating to 100℃. Add 0.5g of polyvinyl alcohol (PVA) as a dispersant and continue stirring for 30 minutes. Then add 1.0g of hexamethylenetetramine (HMTA) as a crosslinking agent and continue stirring for 4 hours to obtain a prepolymer solution. After the reaction is complete, transfer the product from the three-necked flask to a centrifuge tube and centrifuge at 4000rpm for 10 minutes, discarding the supernatant. Wash the precipitate three times with deionized water, adding 50mL of deionized water each time, shaking well, and then centrifuging. Then wash three times with anhydrous ethanol, adding 50mL of anhydrous ethanol each time, shaking well, and then centrifuging. Transfer the washed precipitate to a petri dish and dry it in a vacuum drying oven at 105℃ for 24 hours to obtain dried phenolic resin balls.

[0079] Step 2: Disperse the dried phenolic resin balls in a 4-6 g / L tannic acid ethanol solution; stir the reaction at 300 rpm for 12 hours at room temperature using a magnetic stirrer to allow tannic acid to be fully adsorbed onto the surface of the phenolic resin balls; after the reaction is complete, wash the balls three times with deionized water and ethanol respectively to remove unreacted tannic acid and obtain tannic acid-modified phenolic resin balls.

[0080] Step 3: The tannic acid-modified phenolic resin spheres were dispersed in 100 mL of 0.05 mol / L ZrCl4 solution; the pH of the solution was adjusted to 5-6 with dilute hydrochloric acid, and the mixture was stirred at 300 rpm with a magnetic stirrer for 24 hours at room temperature to allow the Zr... 4+ It undergoes a coordination reaction with oxygen atoms in tannic acid to form a metal-organic framework (MOF) structure; after the reaction is complete, it is washed three times with deionized water and ethanol respectively to remove uncoordinated metal ions, and metal-coordinated phenolic resin balls are obtained.

[0081] Step 4: Place the metal-coordinated phenolic resin balls into a high-temperature carbonization furnace and heat them to 800°C at a rate of 5°C / min. Carbonize them for 2 hours under argon protection (argon flow rate of 50 mL / min) to obtain metal-coordinated phenolic resin carbon balls. Allow them to cool naturally to room temperature, remove the metal-coordinated phenolic resin carbon balls, wash them three times with deionized water and ethanol respectively, and dry them for later use.

[0082] Step 5: Disperse the metal-coordinated phenolic resin carbon spheres obtained in Step 4 in 100 mL of 0.1 mol / L boric acid aqueous solution; adjust the pH to 9-10 with sodium hydroxide solution, and stir the reaction at room temperature for 24 hours to allow the boric acid to react as B(OH)4. - The boric acid exists in the form of tannic acid template molecules and adsorbs onto the tannic acid and metal coordination sites on the surface of the carbon spheres. After the reaction, the spheres are washed three times with deionized water to remove unadsorbed boric acid. The carbon spheres with adsorbed boric acid template molecules are dispersed in an ethanol solution containing 0.1 mol / L ethylene glycol dimethacrylate and 0.02 mol / L potassium persulfate. The mixture is stirred at 60°C for 6 hours to allow the crosslinking agent to polymerize under the action of the initiator, thus fixing the boric acid template molecules onto the surface of the carbon spheres. After the reaction, the spheres are washed three times each with ethanol and deionized water to remove unreacted crosslinking agent and initiator.

[0083] Step 6: Disperse the cross-linked polymerized carbon spheres obtained in Step 5 in 100 mL of 0.1 mol / L hydrochloric acid solution; adjust the pH of the solution to 2-3, stir the reaction at room temperature for 2 hours to elute the boric acid template molecules from the surface of the carbon spheres; wash three times with deionized water and ethanol respectively to remove residual acid, and dry to obtain a metal-coordinated carbon sphere material with molecular imprints.

[0084] The carbon sphere materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested, and the test results are shown in Table 1.

[0085] Table 1

[0086]

[0087]

[0088] Figure 2 This is a comparison chart showing the adsorption selectivity of the materials prepared in Examples 1-3 and Comparative Examples 1-4 for boric acid, oxalic acid, and citric acid. Figure 3 The figures show a comparison of the stability of the materials prepared in Examples 1-3 and Comparative Examples 1-4 after multiple adsorption-desorption cycles. Regarding the comparison of examples, the comparison between Example 1 and Example 2 illustrates the effect of carbonization temperature. When the carbonization temperature decreased from 800℃ to 700℃, the specific surface area of ​​the material decreased from 580 m² / m³. 2 / g decreased to 450m2 The average pore size increased from 2.8 nm to 3.2 nm. This is because the lower carbonization temperature resulted in incomplete carbonization, low graphitization of the carbon spheres, and poor development of the internal pore structure. Regarding adsorption performance, the adsorption capacity of boric acid decreased from 48.6 mg / g to 35.2 mg / g, while the adsorption capacity of oxalic acid and citric acid increased. The selectivity coefficient decreased from 9.8 to 7.2, indicating that the lower carbonization temperature led to a reduction in effective molecularly imprinted holes and a decrease in the specific recognition ability of boric acid. A comparison between Example 1 and Example 3 shows the effect of different metal ion types. In Example 3, FeCl3 was used instead of ZrCl4, resulting in a decrease in the specific surface area to 520 m². 2 / g, the pore size increased to 4.5nm, and the difference in MOF structure formed by different metal ions resulted in a loose pore structure. The boric acid adsorption capacity was 42.5mg / g, and the selectivity coefficient decreased to 8.5, indicating that Zr 4+ It is superior in forming a structure that facilitates the selective adsorption of boric acid.

[0089] In comparative examples, Comparative Example 1, without the cross-linking polymerization step, showed a boric acid adsorption capacity of only 12.3 mg / g and a selectivity coefficient of 1.2, significantly lower than that of Example 1. In Example 1, the cross-linking polymerization used ethylene glycol dimethacrylate initiated by potassium persulfate to form a three-dimensional network structure that immobilized the boric acid template molecules. In contrast, Comparative Example 1 only underwent physical adsorption of boric acid, failing to form effective molecularly imprinted holes, resulting in a significant decrease in specific adsorption capacity. Comparative Example 2 did not form a metal-organic framework (MOF) structure, exhibiting poor stability; after multiple cycles, some carbon spheres broke down, resulting in a boric acid adsorption capacity of 18.7 mg / g and a selectivity coefficient of 2.5. In Example 1, Zr... 4+ The MOF structure formed with tannic acid enhances stability and provides a specific adsorption environment. Comparative Example 2 lacks this structure, resulting in reduced adsorption capacity and selectivity. Comparative Example 3 does not introduce molecular imprinting, and its specific surface area and pore size are similar to those of Example 3, but its boric acid adsorption capacity of 25.8 mg / g and selectivity coefficient of 1.8 are significantly lower than those of Example 1, indicating that molecular imprinting endows the material with the specific recognition ability of boric acid.

[0090] In summary, the molecularly imprinted metal-coordinated carbon spheres prepared by this invention have significant impacts on their properties due to factors such as the introduction of molecular imprinting, cross-linking polymerization, formation of metal coordination structures, and carbonization temperature during the preparation process. Comparative Example 4, which underwent tannic acid modification and metal coordination before carbonization, exhibited a specific surface area of ​​400 m². 2 The adsorption capacity of boric acid was 22.4 mg / g, and the selectivity coefficient was 2.3, both lower than those of Examples 1-3. This indicates that tannic acid modification and metal coordination after carbonization are more conducive to the formation of a stable MOF structure, thereby improving the adsorption performance and selectivity of the material. The stability of Comparative Example 4 was 78%, also lower than that of Examples 1-3, suggesting that modification and coordination before carbonization may lead to more structural damage in the material during repeated cycles.

[0091] Any parts not mentioned in this invention can be achieved by referring to existing technologies.

[0092] Those skilled in the art should recognize that the above embodiments are only used to illustrate this application and are not intended to limit this application. Any appropriate changes and variations made to the above embodiments within the essential spirit and scope of this application fall within the scope of protection claimed in this application.

Claims

1. A method for preparing molecularly imprinted metal-coordinated carbon spheres for removing boric acid from water, characterized in that, The steps are as follows: a. Preparation of phenolic resin balls using formaldehyde and phenol as raw materials; b. The phenolic resin balls are carbonized at a carbonization temperature of 700-900℃ under argon protection to obtain phenolic resin carbon balls. c. Disperse phenolic resin carbon balls in tannic acid ethanol solution and react for a period of time to allow tannic acid to be fully adsorbed on the surface of phenolic resin carbon balls, thereby obtaining tannic acid modified phenolic resin carbon balls. d. Disperse tannic acid-modified phenolic resin carbon spheres in a metal salt solution, adjust the pH of the solution to 5-6, and stir the reaction at room temperature for 20-25 hours to allow the metal ions in the metal salt solution to coordinate with the oxygen atoms in the tannic acid to form a metal-organic framework structure. After the reaction is complete, metal-coordinated phenolic resin carbon spheres are obtained. e. Disperse metal-coordinated phenolic resin carbon spheres in a boric acid solution, so that the boric acid is in the form of B(OH)4 - The boric acid template molecules exist in the form of tannic acid and are adsorbed onto the tannic acid and metal coordination sites of the metal-coordinated phenolic resin carbon spheres to obtain carbon spheres adsorbed with boric acid template molecules; the carbon spheres adsorbed with boric acid template molecules are dispersed in an ethanol solution containing a crosslinking agent and an initiator, and a polymerization reaction is carried out at a certain temperature to further fix the boric acid template molecules to obtain crosslinked polymerized carbon spheres. f. Disperse the cross-linked polymerized carbon spheres in an acidic solution, elute the boric acid template molecules, and dry to obtain a metal-coordinated carbon sphere material with molecular imprinting.

2. The method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water according to claim 1, characterized in that: The specific steps of step a are as follows: formaldehyde and phenol are mixed and stirred at a molar ratio of 1.2:1, heated to 90-110℃, a dispersant is added and stirred for 20-40 minutes, a crosslinking agent is added and stirred for 3-5 hours; after the reaction is completed, the crosslinked product is transferred to a centrifuge tube, the supernatant is discarded by centrifugation, and the collected prepolymer solution is washed and dried to obtain phenolic resin balls.

3. The method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water according to claim 2, characterized in that: The dispersant is polyvinyl alcohol, and the crosslinking agent is hexamethylenetetramine.

4. The method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water according to claim 1, characterized in that: In step b, the carbonization heating rate is 4-6℃ / min, and the carbonization time is 1-3h. After carbonization, the carbon balls are naturally cooled to room temperature, and the resulting carbon balls are washed and dried with deionized water and ethanol to obtain phenolic resin carbon balls.

5. The method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water according to claim 1, characterized in that: In step c, the solid-liquid ratio of phenolic resin carbon balls to tannic acid ethanol solution is 1:10 g / mL; the concentration of tannic acid ethanol solution is 4-6 g / L; and the two are stirred at 200-400 rpm for 10-15 h.

6. The method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water according to claim 1, characterized in that: In step d, the metal salt solution is either a ZrCl4 solution or a FeCl3 solution.

7. The method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water according to claim 6, characterized in that: The solid-liquid ratio of tannic acid-modified phenolic resin carbon spheres to metal salt solution is 1:100 g / mL; the metal salt solution is ZrCl4 solution with a concentration of 0.05 mol / L.

8. The method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water according to claim 1, characterized in that: In step e, the solid-liquid ratio of the metal-coordinated phenolic resin carbon spheres to the boric acid solution is 1:30 g / mL; the concentration of the boric acid solution is 0.1 mol / L; the crosslinking agent is 0.1 mol / L ethylene glycol dimethacrylate; and the initiator is 0.02 mol / L potassium persulfate.

9. A method for preparing a molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water, as described in claim 1, characterized in that: In step f, the acidic solution is a 0.1 mol / L hydrochloric acid solution, and the pH is adjusted to 2-3 by the hydrochloric acid solution.

10. A molecularly imprinted metal-coordinated carbon sphere material for removing boric acid from water, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Imprinted molecular polymer and molecularly imprinted electrochemical sensor based on boric acid groups

    CN106645324A

  • Molecularly imprinted glycosyl mesoporous silica microspheres and preparation method and application thereof

    CN113426427A